HUBUNGAN PENGETAHUAN TENTANG HIPERTENSI DENGAN PENGENDALIAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI POLIKLINIK PENYAKIT DALAM RSUD DR.MOEWARDI SURAKARTA - Wulansari, Jayanti; Ichsan, Burhannudin; Usdiana, Devi (Biomedika, 2013)
Nowadays, hypertension becomes the main problem in the world. Uncontrolled hypertension remains the main health problem. One of the problems that cause uncontrolled blood pressure is the less knowledge of hypertension. Patientâs knowledge and awareness in hypertension is the important factor to control the blood pressure. The aim of this study is to know the relation between hypertension knowledge and blood pressure restraint to hypertension patient in the Internist Polyclinic RSUD dr.Moewardi Surakarta. This research used analytic survey method in cross sectional approach. It took 57 sample of hypertension patient. It used purposive sampling technique. This research used Chi Square statistic test. In forty two patients (73,7%) with well-knowledge, 31 patients hypertension (73,8%) have controlled-blood pressure and uncontrolled blood pressure is 11 patients (26,2%). Whereas, in 15 patients (26,3%) who has lack-knowledge found controlled-blood pressure in 6 patients (40%), and uncontrolled blood pressure in 9 patients (60%). There was not found less-knowledge patients. The Chi Square test found signifi cance probability (p)= 0,019. There is relation between hypertension knowledge and controlling blood pressure.Keywords: knowledge, hypertension, controlling blood pressure